Utilization of Rice Husk Cellulose as a Magnetic Nanoparticle Biocomposite Fiber Source for the Absorption of Manganese (Mn2+) Ions in Peat Water - Emil Zacky Effendi; Yudhi Christian Hariady; Muhammad Daffa Salaahuddin; Chairul Irawan; Iryanti Fatyasari Nata (Jurnal Kimia Sains dan Aplikasi, 2019)
Rice husk (RH) is an agricultural waste that contains cellulose. Rice husk fiber (RHF) can be used as a source of fiber in the manufacture of magnetic nanoparticle biocomposite. The purpose of this study is to synthesize and characterize magnetic nanoparticle biocomposite used as an adsorbent and evaluate its performance on the adsorption of  Mn2+ ions and Total Suspended Solid (TSS) in peat water. Rice husk fiber was delignified to eliminate lignin levels. Furthermore, the biocomposite was made through the solvothermal method with and without the addition of hexanediamine. The products produced are two types of adsorbents, namely magnetic nanoparticle biocomposite with an amino group (RHB-MH) and rice husk fiber biocomposite without an amino group (RHB-M). These biocomposites were used to adsorb Mn2+ ions in peat water. Evaluations were carried out at pH 5, 6, 7, and 8 with an optimum adsorption time of 60 minutes. The solutions at the time of adsorption were evaluated to determine the optimum conditions of the adsorption process carried out. The observation of magnetic nanoparticle biocomposite based on the analysis of Scanning Electron Microscopy (SEM) shows magnetic nanoparticles formed on the surface of rice husk fiber with a diameter of 30-50 nm. X-Ray Diffraction (XRD) analysis showed that the delignification of rice husk increased Crystallinity Index (CrI) by 64.98% and reduced silica content by 78%. Fourier Transform Infra-Red (FT-IR) spectrometer show absorption peak at 570 cm-1 for Fe-O bonds and Fe3O4 peak around 1627 cm−1, indicating the presence of N-H bending. The optimum condition for Mn2+ adsorption was achieved at pH 5 and 60-minutes duration with an adsorption capacity of 54.7 mg/g and 190.78 mg/g for RHB-M and RHB-MH. The TSS reduction achieved the effectiveness of 60.2% and 90.3% for BSP-M and BSP-MH, respectively.